IMPLEMENTATION OF INDIVIDUAL COUNSELING SERVICES FOR CHILDREN FROM BROKEN HOME FAMILY AT SMP NEGERI 2 DOLOK SIGOMPULON - Amnah Sari Hasibuan; Saiful Akhyar; Nurussakinah Daulay (Erudio Journal of Educational Innovation, 2022)
The purpose of this study was to determine how individual counseling services for children from Broken Home families were implemented at SMP Negeri 2 Dolok Sigompulon. The qualitative research method was used in this thesis. The participants in this study were eight students from Broken Home Families at SMP Negeri 2 Dolok Sigompulon. Interviews (interviews), observations (observations), and documentation were utilized to collect data. While data reduction, data presentation, and making conclusions are the data analysis strategies used. According to the findings of this study, guidance and counseling teachers use individual counseling services to assist students in dealing with the problem of broken homes.  Individual counseling services are carried out continuously to solve problems faced by students. It was found from the findings of interviews done by researchers with school principals, Counseling Guidance teachers, and students, that students were increasingly able to face the problems they faced to attain their future life objectives with the availability of individual counseling services. Individual counseling services increase changes in behavior and attitudes, as well as increase learning accomplishment, indicating a positive direction for students.